EFEKTIVITAS PEMBIAYAAN MURABAHAH SEKTOR PERTANIAN DALAM MENINGKATKAN PENDAPATAN HASIL PERTANIAN NASABAH DI KABUPATEN PASAMAN BARAT di PT BPRS MENTARI PASAMAN SAIYO - Zuhriya Ulfah; Rika Widianita (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
Agricultural sector murabahah financing at BPRS Mentari Pasaman Saiyo faces several challenges, such as customers' lack of understanding about financing agreements leading to inappropriate implementation, misuse of financing objectives for consumptive needs, and customers' difficulties in fulfilling installment obligations due to income fluctuations. This study uses a qualitative descriptive method to analyze the effectiveness of agricultural sector murabahah financing at BPRS Mentari Pasaman Saiyo. The research findings indicate that murabahah financing has shown fairly good effectiveness in increasing customers' agricultural income. The targeted, transparent, and fair financing distribution process has increased customer satisfaction and reduced the risk of default. To improve financing effectiveness, BPRS Mentari Pasaman Saiyo needs to maintain well-established processes and improve aspects that need enhancement, such as planning utility and financing scope. By doing so, BPRS can continue to support agricultural sector development and improve community welfare.